2012
DOI: 10.4321/s1699-695x2012000300005
|View full text |Cite
|
Sign up to set email alerts
|

La demora diagnóstica en el cáncer colorrectal en función del medio de procedencia

Abstract: Determinar la existencia de diferencias en la demora diagnóstica del cáncer colorrectal atribuible al proveedor en función del medio de procedencia (rural/urbano) y valorar la repercusión que esa demora pudiera producir sobre la extensión tumoral medida mediante la estadificación. Diseño del estudio: Estudio observacional transversal. Emplazamiento: Atención sanitaria en la provincia de Orense. Participantes: Todos los pacientes diagnosticados de cáncer colorrectal registrados en el Complejo Hospitalario de Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
1
1
Order By: Relevance
“…No difference in provider delay was found between rural and urban areas, which is again counter to previously published results [ 8 , 13 , 28 ]. Differences were detected, however, between patients living in locations with a health center and those living > 20 km from the nearest health center.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…No difference in provider delay was found between rural and urban areas, which is again counter to previously published results [ 8 , 13 , 28 ]. Differences were detected, however, between patients living in locations with a health center and those living > 20 km from the nearest health center.…”
Section: Discussioncontrasting
confidence: 99%
“…The last two reasons are typically called provider delay. Studies have shown that individuals living in more disadvantaged locations (rural environments) have more limited access to the healthcare system and thus worse outcomes in various diseases [ 8 ]. These difficulties have also been observed during the current COVID-19 pandemic [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%